Implementation of Hybrid Contracts in the Gold Pawn Practice in Sharia Pawnshops - Dimas Kenn Syahrir; Erika Amelia (Jurnal Iqtisad, 2023)
The hybrid contract in sharia pawn practice is very unique. This gives rise to different views on the transaction model. Several contracts are often applied in hybrid contract of sharia pawn practice include qardh, rahn, and ijarah. In an ijarah contract of sharia pawn, there is indication of irrelevance in the calculation of ujrah from the clause of the fatwa No.25/DSN-MUI/III/2002 concerning Rahn. This research intends to examine the implementation of hybrid contract in sharia pawn practices by raising the case of gold pawn referring to clause of the fatwa. This study applies a qualitative research paradigm with data characteristics consisting of concepts and qualitative statements. The sources of data were obtained from the implementation of sharia pawn practice in several sharia financial institutions and pawnshop companies, contract concepts, and DSN MUI fatwas. From this study, it was found that the rahn and qardh contracts in Islamic pawnshops complied with the clause of the DSN fatwa No.26/DSN-MUI/III/2002 concerning gold rahn. However, there is a potential for riba practices in ijarah contract in sharia pawn that conflict with the DSN fatwa No.25/DSN-MUI/III/2002 concerning Rahn. The potential for riba is indicated from the calculation of ujrah based on the amount of loans.